ANALISIS TITIK PULANG POKOK USAHA SAMBAL IKAN ROA PADA INDUSTRI “RAJA BAWANG” DI KOTA PALU - Aprilia Umar, Ayu Silviani; Muis, Abdul (AGROTEKBIS, 2018)
This study aimed to determine the production rate to reach break event point of roa fish sauce business of Raja Bawang Industry in Palu city and to determine the income and revenue of the roa fish sauce business. The exact location of the industry is in A.R. Saleh street No. 33. The study was conducted in July 2016. The respondents consisted of one leader of the industry and two employees from the production section and two other employees from packaging section.Data was analyzed using the Break Event Point analysis. The income generated from 200g packaging of the roa fish sauce business was IDR 16,800,000/month with the production cost of IDR 11,258,416/month and the revenue of IDR 5,541,584/month. The Break Event Point reached for the 200g roa fish packaging was at the production rate of 270 packages with the selling price of IDR 35,000/package, thus the revenue generated from this selling price was 9,450,000/month.